1996
DOI: 10.2136/sssaj1996.03615995006000040044x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperiod Influences on Nutrient Dynamics in Decomposing Litter of a Floodplain Forest

Abstract: Lack of clarity regarding the relationship between hydroperiod and decomposition dynamics has long been a barrier to the development of a clear understanding of floodplain biogeochemistry. Relationships between hydroperiod and decomposition processes were investigated using a controlled, field approach on the Ogeechee River floodplain in south Georgia. The study intent was to develop cause‐effect relationships between specific flooding regimes and decomposition parameters. Microcosms designed to manipulate flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 0 publications
4
25
1
1
Order By: Relevance
“…For instance, van der Valk et al (1991) reported a greater CPOM decomposition rate in a variable flooding treatment than a more constant water level. Other studies confirmed the influence of water level variability on CPOM decomposition (Connor and Day 1991, Neckles and Neil1 1994, Lockaby et al 1996, Atkinson and Cairns 2001, a relationship that is linked to alternating periods of saturation and aerobic respiration (Brinson et al 1981). In our study, CPOM decomposition rates were strongly related to hydrologic regime, but decomposition rates in the 12-and 155-year-old wetlands were likely impeded by desiccation, as reported by Atkinson and Cairns (2001) and van der Valk et al (1991).…”
Section: Daysmentioning
confidence: 80%
“…For instance, van der Valk et al (1991) reported a greater CPOM decomposition rate in a variable flooding treatment than a more constant water level. Other studies confirmed the influence of water level variability on CPOM decomposition (Connor and Day 1991, Neckles and Neil1 1994, Lockaby et al 1996, Atkinson and Cairns 2001, a relationship that is linked to alternating periods of saturation and aerobic respiration (Brinson et al 1981). In our study, CPOM decomposition rates were strongly related to hydrologic regime, but decomposition rates in the 12-and 155-year-old wetlands were likely impeded by desiccation, as reported by Atkinson and Cairns (2001) and van der Valk et al (1991).…”
Section: Daysmentioning
confidence: 80%
“…It also is possible that there was more FET than is ideal for decomposition. Lockaby et al (1996) found that a single, relatively brief inundation period had the greatest positive influence on decomposition rate. As conditions change from flooded to exposed or vice versa, invertebrate and microbial communities change and processing is interrupted (Barlocher et al 1978).…”
Section: Brookside Aldermentioning
confidence: 91%
“…Litter was carefully removed from the interior of the bag and sediment was rinsed off. We oven-dried (65 C) leaf litter for about one week until a constant mass was reached (Morris & Lajtha 1986;Lockaby et al 1996), recorded mass, and ground the litter to a powder in a 2-mm mesh Wiley Mill (Thomas Scientific, http://www.thomassci.com). Three subsamples of the ground litter were then incinerated to calculate ash-free dry mass (AFDM).…”
Section: Decomposition Proceduresmentioning
confidence: 99%
“…Rates are lower where permanently flooded, permanently dry, or even alternating aerobic and anaerobic conditions prevail. Lockaby et al (1996) suggested that brief flooding regimes, followed by moist but well aerated conditions, maximized mass and carbon (C) loss. Brinson (1981) also has suggested that, where decomposition is not limited by either oxygen availability or moisture, temperature is the "single most important variable" governing mass loss.…”
mentioning
confidence: 99%